A Concise Asymmetric Synthesis of Sex Pheromone of Euproctis pseudoconspersa (Strand) and Its Enantiomer - Biyu An; Shengli Liu; Jianan Wang; Dan Liu; Qinghua Bian; Jiangchun Zhong (Molecules)
The tea tussock moth, Euproctis pseudoconspersa (Strand), is a serious pest, and its sex pheromone is (R)-10,14-dimethylpentadecyl isobutyrate. A new and concise asymmetric synthesis of the sex pheromone and its enantiomer was accomplished. The chiral methyl of the pheromone was introduced by Evans’s template, while the extension of the carbon chain was achieved through Li2CuCl4-catalyzed coupling of chiral tosylate with Grignard reagent.